hH-Rev107, a class II tumor suppressor gene, is expressed by post-meiotic testicular germ cells and CIS cells but not by human testicular germ cell tumors. - Siegrist, Sylvie (Nature Publishing Group, 2001)
By systematic analysis of a human testis library, we have isolated the hH-Rev107-3 cDNA, identical to hH-Rev107-1 cDNA, which was previously described as a class II tumor suppressor gene (Husmann et al., 1998). In this study, two transcripts (1 and 0,8 kb) were detected by Northern blot in all human tissues, excepted in thymus. The strongest expression was found in testis, skeletal muscle and heart. These two mRNA are probably transcribed from only one gene that we mapped to the q12–q13 region of the chromosome 11. In human testis, hH-Rev107 gene expression was localized, by in situ hybridization, within the round spermatids. To investigate a possible role for hH-Rev107 protein in testicular malignant growth, we examined the expression of this gene in germ cell tumors. A strong hH-Rev107 gene expression was observed in normal testis as well as in samples with preinvasive carcinoma in situ but was completely absent in overt tumors, both seminomas and non-seminomas. By in situ hybridization, CIS was found hH-Rev107 positive and tumor negative. A semi-quantitative assessment of hH-Rev107 mRNA level in testicular germ cell tumors, by RT-PCR, exhibited a 9-fold decrease in the gene expression. No gross structural aberrations of hH-Rev107 gene were detected in these human primary tumors. The results suggest that down-regulation of hH-Rev107 may be associated with invasive progression of testicular germ cell tumors.